2020
DOI: 10.2147/nss.s243882
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Between Sleep Duration, Asthma-Related Episodes/Attacks and Emergency Department Visits</p>

Abstract: Background: Inadequate sleep duration potentially increases the risk of allergic asthma; yet, the effect of different sleep duration on asthma-related episodes/attacks and emergency department (ED) visits has remained unclear. The purpose of this study is to evaluate the association between sleep duration, asthma-related episodes/attacks and ED visits. Methods: This study included 1526 asthma participants from the Behavioral Risk Factor Surveillance System Questionnaire during 2013-2017. Self-reported sleep du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The prevalence of short sleep duration (≤6 h) ranged from 45% to 50.8% in three studies about asthmatics [ 13 15 ], which seemed to be higher than that in the general population. Our previous study also observed that the prevalence of short sleep duration is gradually increasing with the deterioration of asthmatic clinical outcomes [ 14 ]. Short sleep duration may result in some complications such as chronic low-grade inflammation, obesity, and immune dysfunction (see Figure 1 ), which potentially affect the development and acute exacerbation of asthma and lung function impairment.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The prevalence of short sleep duration (≤6 h) ranged from 45% to 50.8% in three studies about asthmatics [ 13 15 ], which seemed to be higher than that in the general population. Our previous study also observed that the prevalence of short sleep duration is gradually increasing with the deterioration of asthmatic clinical outcomes [ 14 ]. Short sleep duration may result in some complications such as chronic low-grade inflammation, obesity, and immune dysfunction (see Figure 1 ), which potentially affect the development and acute exacerbation of asthma and lung function impairment.…”
Section: Introductionmentioning
confidence: 87%
“…Compared with normal sleep duration, short sleep duration seemed to significantly increase the risk of depressive symptoms (adjusted OR = 1.26, 95% CI: 1.11–1.44). Our previous study about the association between sleep duration and asthmatic episodes/attacks had the data about depression in asthmatics [ 14 ]. Secondary analysis was performed to determine the difference in depression between short and healthy sleep duration in asthmatics.…”
Section: Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…Comorbidity profiles potentially affect asthma severity and asthma control levels and brings increased attention to asthma management [7]. The cross-sectional studies indicated that short sleep duration may increase the prevalence of asthma [8], the frequency of asthma-related emergency department visits [9], and lung function impairment [10]. However, only one prospective study has explored the effect of different sleep duration trajectories from adolescence into adulthood on incident asthma in young adults aged 24-32 years [11].…”
Section: Introductionmentioning
confidence: 99%